Indignity in Solihull: an activist response. Issue 2 (2nd April 2016) - Cardy, Simon
ABSTRACT: This paper discusses a short piece of activist social work practice against an austerity measure designed to remove the right of undocumented sans papiers or unaccompanied children at the age of 16 to remain with their out-of-home foster carers. The local authority's elected representatives voted on a proposal to meet a £1.2 million financial budget shortfall by 'encouraging' young people to move out of foster care into less supported, less secure, and ultimately less costly accommodation. The 'revised service model' was an overtly discriminatory policy as it explicitly proposed a differential and less favourable treatment for unaccompanied children in its care compared to, what it termed, its 'local citizen' children who could remain in foster care until they reached the age of 18—or indeed longer in certain more specific circumstances. The paper explores a response taken by a small group of social workers working in a triple alliance with a service user advocacy organisation and a trade union that successfully challenged the policy, whilst reflecting on some of its difficulties and limitations.